2021
DOI: 10.1371/journal.pone.0247270
|View full text |Cite
|
Sign up to set email alerts
|

Effects of patients’ hospital discharge preferences on uptake of clinical decision support

Abstract: The Centers for Medicare and Medicaid Services identified unplanned hospital readmissions as a critical healthcare quality and cost problem. Improvements in hospital discharge decision-making and post-discharge care are needed to address the problem. Utilization of clinical decision support (CDS) can improve discharge decision-making but little is known about the empirical significance of two opposing problems that can occur: (1) negligible uptake of CDS by providers or (2) over-reliance on CDS and underuse of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Such a trial could have shown that the HRRP incentivizes health care providers to prolong the observation status of patients and avoid readmitting certain patient types (Table 1). 5 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Such a trial could have shown that the HRRP incentivizes health care providers to prolong the observation status of patients and avoid readmitting certain patient types (Table 1). 5 …”
mentioning
confidence: 99%
“…Such a trial could have shown that the HRRP incentivizes health care providers to prolong the observation status of patients and avoid readmitting certain patient types (Table 1). 5 Likewise, a computerized simulation-based study of the Centers for Medicare & Medicaid (CMS) issuance of Program-Specific Reports (PSRs) for transplant centers may have illuminated that these reports could halt the growth of kidney transplants. 6 The PSRs provide the public with detailed information about individual patient-level outcomes posttransplantation with the goal of improving the patient's ability to make informed decisions when selecting a transplant center.…”
mentioning
confidence: 99%